Targeting alertness to improve cognition in older adults: A preliminary report of benefits in executive function and skill acquisition. (September 2016) - Van Vleet, Thomas M.; DeGutis, Joseph M.; Merzenich, Michael M.; Simpson, Gregory V.; Zomet, Ativ; Dabit, Sawsan
Abstract: Efficient self-regulation of alertness declines with age exacerbating normal declines in performance across multiple cognitive domains, including learning and skill acquisition. Previous cognitive intervention studies have shown that it is possible to enhance alertness in patients with acquired brain injury and marked attention impairments, and that this benefit generalizes to improvements in more global cognitive functions. In the current preliminary studies, we sought to test whether this approach, that targets both tonic (over a period of minutes) and phasic (moment-to-moment) alertness, can improve key executive functioning declines in older adults, and enhance the rate of skill acquisition. The results of both Experiments 1 and 2 demonstrate that, compared to active control (AC) training, alertness training significantly enhanced performance in several validated executive function measures. In Experiment 2, alertness training significantly improved skill acquisition compared to AC training in a well-characterized speed of processing (SOP) task, with the largest benefits shown in the most challenging SOP blocks. The results of the current study suggest that targeting intrinsic alertness through cognitive training provides a novel approach to improve executive functions in older adults and may be a useful adjunct treatment to enhance benefits gained in other clinically validated treatments.